The interactive role of odor associations in friendship preferences - J. M. Gaby; G. Gunaydin; V. Zayas (Scientific Reports)
Abstract Who we choose to befriend is highly personal, driven by idiosyncratic preferences about other individuals, including sensory cues. How does a person’s unique sensory evaluation of others’ body odor affect friendship formation? Female participants took part in a speed-friending event where they made judgments of friendship potential (FP) following a 4-minute live interaction. Prior to and following the speed-friending event, participants judged the FP of these women based solely on diplomatic odor (including daily perfume/hygiene products) presented on worn t-shirts. Participants also judged FP based on facial appearance (a 100-ms presentation of portrait photographs). Judgments based solely on diplomatic odor predicted FP judgments following in-person interactions, beyond the predictive ability of photograph-based judgments. Moreover, judgments based on the live interaction predicted changes in the second round of diplomatic odor judgments, suggesting that the quality of the live interaction modified olfactory perception. Results were driven more strongly by idiosyncratic preferences than by global perceiver or target effects. Findings highlight the dynamic role of ecologically relevant social olfactory cues in informing friendship judgments, as well as the involvement of odor-based associative learning during the early stages of friendship formation.